Nie tylko kiełbasa wyborcza. Wątki jedzenia w komunikacji politycznej - Małczyński, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Food themes can be an important part of political communication. Indeed, food has significant social functions, including symbolic ones. For example, culinary taste is linked to class distinction, and particular dishes serve as identity markers. This text is devoted to the topic of using broad themes of food in political communication. Two cases will be discussed. The first is Jarosław Kaczynski`s interview on breakfast television. Talking about his favourite foods, the Law and Justice president shaped his image as a patriot and an "ordinary" person. The second case is Sławomir Mentzen`s diverse use of food themes in political communication. New Hope`s chairman uses the theme of food to promote particular political views. At the same time, he is building his image as a politician faithful to certain values and close to his voters.
Keywords: jedzenie; komunikacja polityczna; mediatyzacja; marketing polityczny; Kaczyński, Jarosław (1949- ); Mentzen, Sławomir (1986- ); food; political communication; mediatisation; political marketing